DAMPAK PSIKOLOGIS MINUMAN KERAS PADA REMAJA (Suatu Kajian di Dusun Talang Pemesun Kec. Jujuhan Kab. Bungo Provinsi Jambi) - Khairiyah, Nilil; Kasih, Fitria; Jarudin, Jarudin (Bimbingan dan Konseling, 2013)
The effect of brandy for adolescent (One of the research at Talang Pemesun. The distric of Jujuhan. In the Muaro Bungo at jambiâs province) The focus of this research is in the emotional and in the moral aspects. The goal of this research is to describe how is the development of adolescent emotionalâs that consume of brandy and how is the development of the moral that happened for adolescent that consume of brandy. The design of this research is descriptive qualitative. The informat of this research is the adolescent that consume of brandy consist of three persons. The support informant is a parent. That lives in Dusun Talang Pemesun in collecting thedata is used interview, observation and document of study. And in analizing the data the researcher using three stpes they are: reduction of the data, report of the data and finding conclution. The result of this research is found there is psychology effect in drinking of brady that is in their emotional. That is feeling scary and attitude. And then there are psychology effect of brandy in the moral aspects they are an attitude to their parent. Based on the result of this research the researcher hopes there is a good challenging for the adolescent that consume of brandy for the future.